Eye-Sim - Sundaraj, Kenneth, Assoc. Prof. Dr.; Lam, Chee Kiang (Malaysian Invention and Design Society (MINDS), 2010)
Assoc. Prof. Dr. Kenneth Sundaraj and his team won gold at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.